A Collaborative Model for Advancing Program Level Assessment - Jim Truelove; Allison Langford (Academic Chairpersons Conference Proceedings, 2016)
Learn about implementing a program level assessment model to facilitate transforming the departmental culture from program review orientation to advancing student learning. Discover the advantages of utilizing a collaborative framework to guide faculty through the change process. Useful tools, assessment strategies, templates and the framework will be provided.
Keywords: Assessment; Program Review; Faculty; Collaboration; Academic Leadership